Periodontal and Prosthetic Biologic Considerations to Restore Biological Width in Posterior Teeth - Kina, José Ricardo [UNESP]; Santos, Paulo Henrique dos [UNESP]; Umeda Kina, Eunice Fumico; Umeda Suzuki, Thais Yumi [UNESP]; dos Santos, Pamela Leticia [UNESP] (Lippincott Williams & Wilkins, 2011)
\ The biologic width is an essential dental space that always needs to be maintained to ensure periodontal health in any dental prosthetic restorations. An iatrogenic partial fixed prosthesis constructed in lower posterior teeth predisposed the development of subgingival caries, which induced violation of the biologic width in involved teeth, resulting in an uncontrolled inflammatory process and periodontal tissue destruction. This clinical report describes a periodontal surgical technique to recover a violated biologic width in lower posterior teeth, by crown lengthening procedure associated with free gingival graft procedure, to ensure the possibility to place a modified partial fixed prosthesis in treated area. The procedure applied to recover the biologic width was crown lengthening with some modifications, associated with modified partial fixed prosthesis to achieve health in treated area. The modified techniques in both surgical and prosthetic procedures were applied to compensate the contraindications to recover biologic width by osteotomy in lower posterior teeth. The result, after 4 years under periodic control, seems to achieve the projected goal. Treating a dental diseased area is necessary to diagnose, eliminate, or control all etiologic factors involved in the process. When the traditional methods are not effective to recover destructed tissues, an alternative, compensatory, and adaptive procedure may be applied to restore the sequelae of the disease, applying a restorative method that respects the biology of involved tissues.
Keywords: Diagnose; gingiva; dental caries; periodontitis